Challenges and pitfalls in the perioperative management of mediastinal mass syndrome: an up-to-date review - Leivaditis, Vasileios; Pavlakou, Afroditi; Grapatsas, Konstantinos; Mulita, Francesk; Koletsis, Efstratios; Papatriantafyllou, Athanasios; Galanis, Michail; Katsakiori, Paraskevi F.; Skevis, Konstantinos; Nikolaidis, Eleftherios; Dahm, Manfred; Tasios, Konstantinos; et al. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2024)
The perioperative management of patients undergoing mediastinal mass operations presents a persistent challenge across multiple clinical specialties. General anesthesia administration further increases the risk of perioperative cardiorespiratory decompensation. The interdisciplinary team plays a crucial role in ensuring a safe perioperative period. However, due to the rarity and variability of mediastinal mass syndromes, specific management protocols are lacking. This review aims to outline the multitude of challenges and pitfalls encountered during perioperative management in patients with the mediastinal mass syndrome. We describe diagnostic evaluation, preoperative optimization, intraoperative considerations, and postoperative care strategies, emphasizing the paramount significance of a multidisciplinary approach and personalized treatment plans. Preoperative multidisciplinary discussions, meticulous anesthetic management, and well-established protocols for emergency situations are pivotal to ensuring patient safety. Healthcare providers involved in the care of patients with mediastinal mass syndrome must grasp these challenges and pitfalls, enabling them to deliver safe and effective perioperative management.